Parliamentary Sovereignty: New Zealand - New Millennium - Grau, Karen (Victoria University of Wellington Law Review, 2002)
The author examines contemporary debates in New Zealand and Australia over the power of the Courts to disregard Statutes and concludes that such a power, if it exists, ought to be exercised cautiously.